Thrombectomy Using the EmboTrap Clot-Retrieving Device for the Treatment of Acute Ischemic Stroke: A Glimpse of Clinical Evidence - Bai, X.; Fu, Z.; Sun, Z.; Xu, R.; Guo, X.; Tian, Q.; Dmytriw, A.A.; Zhao, H.; Wang, W.; Wang, X.; Patel, A.B.; Yang, B.; et al. (American Journal of Neuroradiology, 2022)
BACKGROUND: The EmboTrap Recanalization Device is a novel stent retriever for thrombectomy in the setting of acute ischemic stroke due to large-vessel occlusion.PURPOSE: Our aim was to summarize the safety and efficacy of the EmboTrap Recanalization Device in acute ischemic stroke–large-vessel occlusion through a systematic review and meta-analysis.DATA SOURCES: Medline, EMBASE, the Cochrane Library, Web of Science, and Google Scholar were searched up to April 2022.STUDY SELECTION: Nine observational studies using the EmboTrap Recanalization Device were selected.DATA ANALYSIS: We adapted effect size with 95% CIs for dichotomous data. P value <.05 was statistically significant.DATA SYNTHESIS: The estimated rate of successful recanalization (modified TICI 2b–3) was 90% (95% CI, 86%–95%; I2 = 82.4%); 90-day favorable outcome (mRS 0–2), 53% (95% CI, 42%–63%; I2 = 88.6%); modified first-pass effect, 43% (95% CI, 35%–51%; I2 = 63.7%); and first-pass effect, 36% (95% CI, 29%–46%; I2 = 10.7%). The rate of any intracerebral hemorrhage was 19% (95% CI, 16%–22%; I2 = 0.0%); symptomatic intracerebral hemorrhage, 5% (95% CI, 1%–8%; I2 = 84.6%); and 90-day mortality, 14% (95% CI, 9%–19%; I2 = 79.3%). Subgroup analysis showed higher rates of complete recanalization for EmboTrap II than for the EmboTrap System.LIMITATIONS: The included studies are single-arm without direct comparison with other stent retrievers. Some of the studies recruited had a small sample size and were limited by the retrospective study design. In addition, the uncertain heterogeneity among studies was high.CONCLUSIONS: The EmboTrap Recanalization Device is safe and efficient in treating acute ischemic stroke due to large-vessel occlusion.AISacute ischemic strokeFPEfirst-pass effectICHintracerebral hemorrhageLVOlarge-vessel occlusionmFPEmodified first-pass effectMTmechanical thrombectomymTICImodified TICIsICHsymptomatic intracerebral hemorrhage